2009
DOI: 10.1073/pnas.0903111106
|View full text |Cite
|
Sign up to set email alerts
|

Engineering botulinum neurotoxin to extend therapeutic intervention

Abstract: Clostridium botulinum neurotoxins (BoNTs) are effective therapeutics for a variety of neurological disorders, such as strabismus, blepharospam, hemificial spasm, and cervical dystonia, because of the toxin's tropism for neurons and specific cleavage of neuronal soluble N-ethylmaleimide-sensitive fusion protein-attachment protein receptors (SNARE) proteins. Modifying BoNT to bind nonneuronal cells has been attempted to extend therapeutic applications. However, prerequisite to develop nonneuronal therapies requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 34 publications
(43 reference statements)
1
51
0
1
Order By: Relevance
“…Botulinum toxin type A is in clinical trials for numerous additional indications, including pain, muscle spasticity, overactive bladder, alopecia areata, benign prostatic hyperplasia and headaches, whereas type B is in clinical trials for spasticity due to cerebral palsy and cervical dystonia [93]. Besides the development of botulinum toxin for more indications, other efforts are aiming to reduce immunogenicity of the material, developing less invasive delivery methods and improving stability of the drug [94,95]. …”
Section: Proteases Are Ubiquitous In Biologymentioning
confidence: 99%
“…Botulinum toxin type A is in clinical trials for numerous additional indications, including pain, muscle spasticity, overactive bladder, alopecia areata, benign prostatic hyperplasia and headaches, whereas type B is in clinical trials for spasticity due to cerebral palsy and cervical dystonia [93]. Besides the development of botulinum toxin for more indications, other efforts are aiming to reduce immunogenicity of the material, developing less invasive delivery methods and improving stability of the drug [94,95]. …”
Section: Proteases Are Ubiquitous In Biologymentioning
confidence: 99%
“…In fact, Botox™ (BoNT/A) treatment is FDA approved, and according to statistics provided by the American Society for Aesthetic Plastic Surgery [11], is one of the top non-surgical cosmetic procedures performed in the United States. Furthermore, to extend BoNT potency for clinical neurology applications, chimeric and modified BoNTs have been generated using protein engineering methods to expedite the toxin’s cellular entry, increase its substrate specificity, and extend its duration of activity in neuronal and possibly non-neuronal cells [9, 1214]. …”
Section: Introductionmentioning
confidence: 99%
“…Although BoNT-A has been considered the obvious serotype to form the basis of engineered proteins, studies of the mechanism by which the light chain of BoNT-A recognizes and cleaves SNAP25 have shown that the light chain of BoNT-A requires a longer substrate and a greater number of residue interactions than, for example, BoNT-E. [95] As BoNT-E has a more straightforward interaction with SNAP25, this may make a more suitable toxin to engineer, in particular, for studies seeking to alter the substrate specificity and extend the therapeutic application beyond neurologic conditions. [96] However, for reasons that have yet to be established, the duration of action of BoNT-E is much shorter than that of BoNT-A, which is an additional important consideration when identifying the most suitable molecule to modify for clinical application.…”
Section: Future Prospects: Potential Therapeutic Use Of Re-engineeredmentioning
confidence: 99%